2017
DOI: 10.1007/978-1-4939-6952-4_12
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Proteomic Analysis of Microvesicles and Exosomes from HT22 Cells and Primary Neurons

Abstract: Exosomes and microvesicles are extracellular vesicles (EVs) released by most cell types. The role of EVs as a method of intercellular communication has led to these vesicles becoming a major area of interest in a variety of scientific fields including neuroscience. Emerging evidence is now demonstrating that the biomolecular composition of EVs, especially exosomes, can play a role in the progression of disease including various neurodegenerative diseases and cancer. In addition to the miRNA profiles of EVs, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Our proteomic analysis further revealed that exosomes-derived from GIST cells carry several common exosomal proteins, tumor specific markers, and previously unreported proteins indicating that GDE display shared proteomic features with exosomes-derived from other cells types, while conserving tumor identity. Many proteomic studies, aiming to identify tumor specific markers, took advantage of the homogeneous distribution profiles of exosomes produced by various cultured cell types (102)(103)(104)(105)(106)(107). Yet, translation and validation of these findings using in vivoderived exosomes are still very challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Our proteomic analysis further revealed that exosomes-derived from GIST cells carry several common exosomal proteins, tumor specific markers, and previously unreported proteins indicating that GDE display shared proteomic features with exosomes-derived from other cells types, while conserving tumor identity. Many proteomic studies, aiming to identify tumor specific markers, took advantage of the homogeneous distribution profiles of exosomes produced by various cultured cell types (102)(103)(104)(105)(106)(107). Yet, translation and validation of these findings using in vivoderived exosomes are still very challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The cargoes contained within EVs reflect both the intracellular origin of the cargo as well as the cell type from which the vesicle was derived. We refer readers to the many profiling studies which have been published on this subject for further information . Prototypical exosome markers include tetraspannins such as CD9, CD63 and CD81, and ESCRT proteins Alix and TSG101 .…”
Section: Functional Cargoes In Microvesicles Derived From Tumor Cellsmentioning
confidence: 99%
“…We refer readers to the many profiling studies which have been published on this subject for further information. 36,66,[94][95][96][97][98][99][100] Prototypical exosome markers include tetraspannins such as CD9, CD63 and CD81, and ESCRT proteins Alix and TSG101. 37,101 Unique and universal MV markers are somewhat less well-defined.…”
Section: Functional Cargoes In Microvesicles Derived From Tumor Cellsmentioning
confidence: 99%
“…In these cells, hTERT mRNA was translated into an active form that transforms them into telomerase-positive cells [122]. Of interest, hTERT expression in hTERT negative cells affected their biological properties towards a tumor like-phenotype, characterized by extended or unlimited life span, prevention and reversal of senescence, resistance to DNA damage, and prevention of apoptosis [19,123]. …”
Section: Role Of Evs In the Malignancy-microenvironment Cross-talkmentioning
confidence: 99%
“…In some cases, EV cytoplasmic and surface content suggest a degree of specific cellular packaging into EVs [6,19]. …”
Section: Introductionmentioning
confidence: 99%